Prostaglandin E2 Impairs P2Y2/P2Y4 Receptor Signaling in Cerebellar Astrocytes via EP3 Receptors - Paniagua-Herranz, Lucía; Gil-Redondo, Juan C.; Queipo, Ma José; González-Ramos, Silvia; Boscá, Lisardo; Pérez-Sen, Raquel; Miras-Portugal, Ma Teresa; Delicado, Esmerilda G. (Frontiers in Pharmacology, 2017)
Prostaglandin E2 (PGE2) is an important bioactive lipid that accumulates after tissue damage or inflammation due to the rapid expression of cyclooxygenase 2. PGE2 activates specific G-protein coupled EP receptors and it mediates pro- or anti-inflammatory actions depending on the cell-context. Nucleotides can also be released in these situations and they even contribute to PGE2 production. We previously described the selective impairment of P2Y nucleotide signaling by PGE2 in macrophages and fibroblasts, an effect independent of prostaglandin receptors but that involved protein kinase C (PKC) and protein kinase D (PKD) activation. Considering that macrophages and fibroblasts influence inflammatory responses and tissue remodeling, a similar mechanism involving P2Y signaling could occur in astrocytes in response to neuroinflammation and brain repair. We analyzed here the modulation of cellular responses involving P2Y2/P2Y4 receptors by PGE2 in rat cerebellar astrocytes. We demonstrate that PGE2 inhibits intracellular calcium responses elicited by UTP in individual cells and that inhibiting this P2Y signaling impairs the astrocyte migration elicited by this nucleotide. Activation of EP3 receptors by PGE2 not only impairs the calcium responses but also, the extracellular regulated kinases (ERK) and Akt phosphorylation induced by UTP. However, PGE2 requires epidermal growth factor receptor (EGFR) transactivation in order to dampen P2Y signaling. In addition, these effects of PGE2 also occur in a pro-inflammatory context, as evident in astrocytes stimulated with bacterial lipopolysaccharide (LPS). While we continue to investigate the intracellular mechanisms responsible for the inhibition of UTP responses, the involvement of novel PKC and PKD in cerebellar astrocytes cannot be excluded, kinases that could promote the internalization of P2Y receptors in fibroblasts.